Company Size Asset Structure and Share Ownership Affect Capital Structure in the Property Sector Listed on the Indonesia Stock Exchange for the Period 2017-2021 - Suhayati*, Ely; Sihole, Krismawati Br (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Komputer Indonesia, 2023)
This study aims to determine the effect of company size, asset structure and share ownership on capital structure in the property sector listed on the IDX for the 2017–2021 period. The method used is a quantitative approach analysis as well as descriptive and verification methods with the sample used, namely the 2017-2021 financial reports with 6 companies, a total of 30 samples. The results showed that the t-test of firm size had a significant negative effect on capital structure, asset structure had no significant positive effect on capital structure, and share ownership had no significant negative effect on capital structure. The results of the F test show the influence of company size, asset structure and share ownership on capital structure. If the three variables experience an increase or decrease, it will have an impact on the Capital Structure which will experience a similar increase or decrease as the three variables. Keywords: Company Size; Assets Structure; Share Ownership; Capital Structure; Property Sector